Addition of Ipragliflozin to Metformin Treatment in Korean Patients with Type 2 Diabetes Mellitus: Subgroup Analysis of a Phase 3 Trial - Kyung-Wan Min (Diabetes & Metabolism Journal, 2017)
BackgroundThis is a subgroup analysis of Korean patients from a phase 3 clinical trial investigating the efficacy and safety of ipragliflozin in patients with type 2 diabetes mellitus inadequately controlled with metformin.MethodsThis multicenter, placebo-controlled, double-blind, parallel-group study was carried out between November 2011 and January 2013. Patients entered a 2-week placebo pretreatment period, followed by a 24-week treatment period with either ipragliflozin (50 mg/day) or placebo, while continuing metformin. Efficacy outcomes (glycosylated hemoglobin [HbA1c], fasting plasma glucose [FPG], and body weight) and safety outcomes (treatment-emergent adverse events [TEAEs]) were measured and compared between the two treatment groups for patients enrolled in all 18 study sites in Korea.ResultsEighty-two Korean patients received ipragliflozin (n=43) or placebo (n=39) during the study period. Mean changes in HbA1c levels from baseline to the end of treatment were –0.97% in the ipragliflozin group and –0.31% in the placebo group, with an adjusted between-group difference of –0.60% (P<0.001). Compared to placebo, FPG and body weight also decreased significantly (both P<0.001) from baseline after treatment in the ipragliflozin group, with between-group differences of –21.4 mg/dL and –1.53 kg, respectively. Decreased weight was the most common TEAE in the ipragliflozin group (7.0%); there were no reports of genital and urinary tract infection.ConclusionIpragliflozin treatment in addition to metformin led to significant improvement in glycemic outcomes and reduction in body weight in Korean patients with type 2 diabetes mellitus, compared with metformin treatment alone; the safety profile was comparable in both groups.